FINANCING OF SOCIAL PROTECTION OF POPULATION IN UKRAINE: TRENDS AND PROSPECTS (INNOVATIVE ECONOMY, 2020)
Kyrylenko O.P., Ohinska A.Yu. FINANCING OF SOCIAL PROTECTION OF POPULATION IN UKRAINE: TRENDS AND PROSPECTSPurpose. The aim of the article is scientific substantiation of theoretical aspects of budget financing of social protection of the population, as well as monitoring of expenditures of state and local budgets for social protection; definition of the problems of effective budget financing of social protection of population in Ukraine.Methodology of research. The methods of general scientific and empirical methods of economic science based on a systematic approach are used in the course of research. In addition, the following methods of scientific knowledge are used to solving the tasks: dialectical and logical, analysis and synthesis, generalization, graphical, statistical analysis – in the process of estimating budget expenditures on social protection, scientific abstraction – in developing proposals for optimizing budget expenditures for social protection and social security.Findings. Summing up the analysis of the trends of budget financing of social protection of the population in Ukraine, it has been found that in spite of a significant increase of corresponding expenditures of state and local budgets, a number of negative phenomena that reduce their effectiveness remain in this area. It is established that in order to increase the well-being of citizens in Ukraine, it would be advisable to develop a comprehensive strategy of social protection of the population based on the theory of institutionalism and the theory of social market economy.Originality. Approaches to developing priorities for building an effective system of social protection of the population, which should provide for unconditional and permanent protection of citizens with disabilities, persons with persistent disability, and based on the principles of targeting, timeliness and motivation, social protection of able-bodied people, are improved. Unlike existing ones, this approach creates prerequisites for reducing the extent of dependency and paternalism in providing social protection.Practical value. The obtained research results are the basis for improving the conceptual model of social protection of the population, and their financing.Key words: social protection; social services; social benefits; social privileges; budget financing; budget expenditures on social protection and social security.
Keywords: Key words; social protection; social services; social benefits; social privileges; budget financing; budget expenditures on social protection and social security.